Time series analysis: trend in late maternal mortality in Brazil, 2010-2019 - Kelly Cristina Almeida Borgonove; Sônia Lansky; Vânia Muniz Nequer Soares; Fernanda Penido Matozinhos; Eunice Francisca Martins; Roberto Allan Ribeiro Silva; Kleyde Ventura de Souza (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: To analyze the temporal trend of the late maternal mortality ratio (LMMR) in Brazil and its geographic regions in the period from 2010 to 2019, an ecological time series study was conducted. Data related to late maternal mortality from information systems of the Brazilian Ministry of Health were used. Statistical analysis used Prais-Winsten autoregressive models. A total of 1,470 late maternal deaths were reported in Brazil, resulting in an LMMR of 5 deaths per 100,000 live births. The late maternal mortality records revealed regional disparities, with the lowest index in the North (3.5/100,000 live births) and the highest in the South (8.3/100,000 live births). The LMMR showed an increasing trend in the country, with a general increase in the LMMR in the period and a mean annual percentage variation of 9.79% (95%CI: 4.32; 15.54). The Central-West region led this increase, with a mean annual percentage change of 26.06% (95%CI: 16.36; 36.56), followed by the North and Northeast regions, with 23.5% (95%CI: 13.93; 33.88). About 83% of the reported late maternal deaths were investigated, and 65.6% were corrected by the Maternal Mortality Committees. These findings highlight the relevance of late maternal mortality as an important indicator for maternal health, which is often invisible. The increase in the LMMR result from the improvement in the quality of the registration of these deaths in recent years in Brazil, and especially from the work of investigating deaths. The fragility of reporting with regional disparities points to the need for a more comprehensive approach that promotes equity and prevention of avoidable late maternal mortality.